Preparation of Substituted Imidazolidinones and Hydantoins by Ring-Expansion of Aziridinones - M. M., Yusoff; Talaty, Erach R.; S. Asmah, Ismail; Gomez, Jaime A.; Keller, Charles E.; Younger, Jean M. (Georg Thieme Verlag, 1997)
Reaction of 1,3-di-tert-butylaziridinone and other di-tert-alkylaziridinones with cyanamides produces an imidazolidinone (3 or 6) bearing the tert-alkyl substituents at positions 1 and 5 only, by selective cleavage of the acyl-nitrogen bond. Treatment of the product from the unsubstituted cyanamide (3) with HNO 2 furnishes the corresponding hydantoin (5), whereas treatment with alkyl halides and base affords another imidazolidinone (7)